2011
DOI: 10.1093/intimm/dxr074
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Th1/Th2/Th17/regulatory T-cell balance in asthmatic pregnancy

Abstract: Asthma is a common chronic disease that may complicate pregnancy and a risk factor for complications; however, immunological mechanisms of the bilateral interactions between asthma and pregnancy are not fully understood. Healthy gestation is characterized by a sensitive balance of T(h)1/T(h)2/T(h)17/regulatory T (Treg) cells that may be altered in asthmatic pregnancy. The aim of this study was to describe the prevalence of these cell subsets in asthmatic compared with healthy pregnancy. The prevalence of T(h)1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
5
28
0
Order By: Relevance
“…These results not only help to understand the etiology of preeclampsia, but also provide a novel rationale for the prevention or intervention of PE via regulation of the balance of Th17/Treg cells. Our results are consistent with recent data by Santner-Nanan et al demonstrating that it is the balance between Tregs and Th17 cells that is critical to maintain tolerance to the fetus and prevents PE patients [36][37][38].…”
Section: Discussion:-supporting
confidence: 94%
“…These results not only help to understand the etiology of preeclampsia, but also provide a novel rationale for the prevention or intervention of PE via regulation of the balance of Th17/Treg cells. Our results are consistent with recent data by Santner-Nanan et al demonstrating that it is the balance between Tregs and Th17 cells that is critical to maintain tolerance to the fetus and prevents PE patients [36][37][38].…”
Section: Discussion:-supporting
confidence: 94%
“…Recent data show the Th17 prevalence is similar in healthy pregnancy to healthy non-pregnant controls. 24 The difference from our study is the previous data focused on the second and third trimesters, while our studies examined the first trimester.…”
Section: Discussionmentioning
confidence: 64%
“…However, several reports have published that circulating Th17 cells were not different between non-pregnant state and each trimester 51 or between non-pregnant period and a certain period of pregnancy. 64,65 Nakashima et al 51 showed that the proportion of decidual Th17 cells was significantly higher than that of circulating Th17 cells in the first trimester. Furthermore, the Th17/Foxp3 + regulatory T-cell ratio was decreased in normal 2nd and 3rd trimester pregnant women as compared to that in healthy non-pregnant women.…”
Section: Human Regulatory T and Th17 Cells During A Menstrual Cycle Amentioning
confidence: 99%